APLIKASI METODE OBJECTIVE MATRIX DAN RESPONSE SURFACE METHODOLOGY UNTUK PENINGKATAN PRODUKTIVITAS - Hadi, Yuswono; Wahyudi, Slamet; Sugiono, Sugiono (JEMIS (Journal of Engineering & Management in Industrial System), 2014)
Continous improvements to increase productivity is compulsory for small medium enterprise. The average value of productivity observed with Objective Matrix, in January-September 2014, is 261 . The main factorwhich affect the value of productivity is the number of defective products produced by Automatic Feeding and Sealing Machine.Approximately, 73.7% of total defective products is leak product. Thus, the main effortto increase value of  productivity is reduce the amount of leak products produced by those macine. After calculating the average value of productivity, design of experiment were performed using central composite design approach. Then measure optimum value for each independent variables using Response Surface Methodology. The optimal values are : Cup Type A ( supplied by PT.Indopack ) , the heater I’s temperature is 256.9 °C and the heater II’s temperature is 258.48 oC . with predicted number of leaked product is 0.86 . By using this setting , the value of productivity turned to 855, far above the average of the previous months.